2016
DOI: 10.1186/s40064-016-1952-8
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory mechanics measured by forced oscillation technique in rheumatoid arthritis-related pulmonary abnormalities: frequency-dependence, heterogeneity and effects of smoking

Abstract: Rheumatoid arthritis (RA)-related pulmonary disorders specifically airway abnormalities and interstitial pneumonia (IP) are important extra-articular manifestations. The forced oscillation technique (FOT) is a useful method to assess respiratory impedance, respiratory resistance (Rrs) and reactance (Xrs), at different oscillatory frequencies during tidal breathing. The aim of this study was to characterize the respiratory mechanics of patients with RA and to relate them to parameters of the pulmonary function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…Therefore, the FOT parameters are largely affected by the presence of small airway disease also in ILD. Moreover, it has been demonstrated that there were no significant differences in the indices of respiratory impedance between the airway lesion dominant and interstitial pneumonia dominant groups in patients with rheumatoid arthritis-related pulmonary abnormalities. 29 This indicates the parenchymal abnormalities did not contribute to the changes in respiratory impedance in ILD.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the FOT parameters are largely affected by the presence of small airway disease also in ILD. Moreover, it has been demonstrated that there were no significant differences in the indices of respiratory impedance between the airway lesion dominant and interstitial pneumonia dominant groups in patients with rheumatoid arthritis-related pulmonary abnormalities. 29 This indicates the parenchymal abnormalities did not contribute to the changes in respiratory impedance in ILD.…”
Section: Discussionmentioning
confidence: 95%
“…CT findings related to ILD features (consolidation, ground glass opacity [GGO], reticular changes, nodular opacity, and honeycomb changes) were graded on a 5‐point scale within the whole lung field as follows: grade 0, finding was absent; grade 1, percentage of involvement of lungs between 1% and 25%; grade 2, percentage of involvement between 26% and 50%; grade 3, percentage of involvement between 51% and 75%; and grade 4, percentage of involvement ≥75% according to criteria of CT patterns defined by Tanaka et al With respect to ILD features, CT patterns were categorized into the following six groups: usual interstitial pneumonia (UIP), nonspecific interstitial pneumonia (NSIP), organizing pneumonia (OP), diffuse alveolar damage (DAD), chronic hypersensitivity pneumonitis (CHP), and unclassifiable pattern. AD features (bronchial wall thickening, bronchial mucous plug, bronchiectasis, bronchiolitis, and air trapping) were also graded on a 5‐point scale as follows: grade 0, finding was absent; grade 1, extent of involvement limited to 1 bronchial segment; grade 2, multiple involvement found in 1 side of lung field; grade 3, multiple involvement found in both lung fields; and grade 4, involvement found diffusely in the whole lung field, according to the criteria of CT patterns defined by Sokai et al Total points for the five features were obtained and a cumulative score was obtained (ILD score and AD score; maximum score of 20 per patient) to represent disease severity. For CT scores, patients were categorized into the following four groups: ILD group (n = 29), AD group (n = 76), Co‐existing group (n = 6), and WDC group (n = 221) in the same manner as described in a previous study .…”
Section: Methodsmentioning
confidence: 99%
“…Other findings observed in pleural lesions (apical cap, pleural thickening, calcification, and pleural effusion) and mediastinal lesions (lymphadenopathy, esophageal dilation, pulmonary artery dilation, and pericardial effusion), as well as nonspecific inflammatory or malignancy findings (intrapulmonary lymph node, calcified nodule, atelectasis, and line shape/cord pattern), were evaluated on a 2‐point scale as follows: grade 0, finding was absent; grade 1, finding was detectable. The extent of emphysema in the whole lung field was also graded according to a previous report on a 5‐point scale, as follows: grade 0, the finding was absent; grade 1, the percentage of involvement of the lungs was between 1% and 25%; grade 2, the percentage of involvement was between 26% and 50%; grade 3, the percentage of involvement was between 51% and 75%; and grade 4, the percentage of involvement was more than 76%. We defined grades 3‐4 emphysema as severe emphysema, and excluded patients with this condition from the study to eliminate the potential influence of chronic obstructive pulmonary disease (COPD) when assessing RAEs.…”
Section: Methodsmentioning
confidence: 99%
“…Impulse oscillometry may be useful, where obstruction can be identified as increased resistance values at lower oscillatory frequencies. This pattern was shown to be present in a retrospective cohort of RA patients in Japan [ [8] , [9] ]. Overall, there is no consensus on what defines RA-related obstructive lung disease, and it should be taken into account that confounders are abundant.…”
Section: Discussionmentioning
confidence: 75%
“…However, some studies have shown increased incidence of obstructive pulmonary function testing in non-smoking RA patients [ 7 ]. In patients where there exist multiple exposures and potential etiologies for pulmonary disease, it can be difficult to isolate and treat a primary diagnosis [ 8 ] With the express consent of the patient, we present a case of complex obstructive lung disease with significant contribution of RA-related small airways disease, which created a diagnostic and therapeutic challenge.…”
Section: Introductionmentioning
confidence: 99%